2019
DOI: 10.1042/bsr20190827
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic roles of the transcriptional expression of exportins in hepatocellular carcinoma

Abstract: Aims: A large number of studies have suggested that exportins (XPOs) play a pivotal role in human cancers. In the present study, we analyzed XPO mRNA expression in cancer tissues and explored their prognostic value in hepatocellular carcinoma (HCC). Methods: Transcriptional and survival data related to XPO expression in HCC patients were obtained through the ONCOMINE and UALCAN databases. Survival analysis plots were drawn with Gene Expression Profiling Interactive Analysis (GEPIA). Sequence alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Therefore, we tried to establish a prognosis/diagnosis-associated mRNA-miRNA-lncRNA ceRNA triple sub-network in hepatocellular carcinoma. By performing survival (OS and RFS) analysis using TCGA hepatocellular carcinoma data, nine genes including three novel genes (CELSR3, GPSM2 and CHEK1) and six "known" genes [CLEC3B (26), DNASE1L3 (27), PTTG1 (28,29), KIF2C (30), XPO5 (31,32) and UBE2S (33,34)] were identified as prognosisassociated genes in hepatocellular carcinoma. The prognostic values of the three novel genes in hepatocellular carcinoma have not been investigated so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tried to establish a prognosis/diagnosis-associated mRNA-miRNA-lncRNA ceRNA triple sub-network in hepatocellular carcinoma. By performing survival (OS and RFS) analysis using TCGA hepatocellular carcinoma data, nine genes including three novel genes (CELSR3, GPSM2 and CHEK1) and six "known" genes [CLEC3B (26), DNASE1L3 (27), PTTG1 (28,29), KIF2C (30), XPO5 (31,32) and UBE2S (33,34)] were identified as prognosisassociated genes in hepatocellular carcinoma. The prognostic values of the three novel genes in hepatocellular carcinoma have not been investigated so far.…”
Section: Discussionmentioning
confidence: 99%
“…By intersecting OS-associated genes and RFSassociated genes, 9 genes (CLEC3B, DNASE1L3, PTTG1, CELSR3, GPSM2, KIF2C, XPO5, UBE2S, and CHEK1) were defined as candidate genes, which were commonly appeared in OS-associated gene set and RFS-associated gene set ( Figure 1A). After reviewing the published literatures and previous studies, we found that 6 of 9 genes [CLEC3B (26), DNASE1L3 (27), PTTG1 (28,29), KIF2C (30), XPO5 (31,32), and UBE2S (33,34)] have been demonstrated to act as promising prognostic biomarkers for hepatocellular carcinoma. The rest three genes (CELSR3, GPSM2, and CHEK1) have not been studied for their prognostic values in hepatocellular carcinoma so far.…”
Section: Celsr3 Gpsm2 and Chek1 Were Identified As Three Novel Progmentioning
confidence: 98%
“…This peptide was derived from the XPO1 (exportin-1/CRM1) protein, which is thought to function as the sole nuclear exporter for many different tumor suppressor and growth regulatory proteins including p53, p27, FOXO1, IkB, cyclin B1, cyclin D1 and survivin (38). XPO1 is overexpressed and associated with poor prognosis in multiple cancers including hematological malignancies and difficult to treat cancers such as pancreatic cancer and HCC (41,43,47). Inhibition of XPO1 is gaining traction as a cancer therapeutic target following clinical trials, and our data suggest it could also be a target for KIR2DS2based NK cell therapeutics (40).…”
Section: Discussionmentioning
confidence: 75%
“…NAPLVHATL, which was identified by three independent, high-quality peptide-spectrum matches ( Figure 3B), is derived from the nuclear export protein exportin-1 (XPO1). This protein is upregulated in many hematological malignancies and solid tumors including HCC, is generally associated with a poor prognosis in cancer and has been successfully targeted in clinical trials of refractory multiple myeloma (38)(39)(40)(41)(42)(43).…”
Section: Kir2ds2 Recognizes a Cancer Associated Antigenmentioning
confidence: 99%
“…In recent years, molecular biology technology and bioinformatics have been widely used in cancer research. This kind of research using public databases containing many samples provides a good way in which to identify tumor biomarkers [20,21]. Here, we systematically explored the roles of RAB family genes in BRCA, including the following characteristics: prognostic values, mRNA expression levels, relationship among expression levels and clinicopathological characteristics, genetic mutations, and gene enrichment.…”
Section: Discussionmentioning
confidence: 99%